Winter infestation of wild birds by ticks and chiggers (Acari: Ixodidae, Trombiculidae) in the Czech Republic - Literak, Ivan; Kocianova, Elena; Dusbabek, Frantisek; Martinu, Jana; Podzemny, Petr; Sychra, Oldrich (Parasitology research, 2007)
In winter months during 2003-2006, wild birds were captured and examined for ticks and chiggers at two sites near Brno, Czech Republic. In total, 1,362 birds, mostly passerines, were examined. The tick Ixodes arboricola Schulze et Schlottke, 1929 was found on 47 (3%) birds of six species. Ixodes ricinus Linnaeus, 1758 was found on 11 (1%) birds of five species. Larvae of chiggers Ascoschoengastia latyshevi (Schluger 1955) were found on 13 (1%) birds of six species. I. arboricola and A. latyshevi associated with hole-nesting birds can appear on birds rather frequently even during winter months. I. ricinus occurs on birds in winter sporadically.
Keywords: Animals; Trombiculidae; Česká republika; infestace roztoči; Passeriformes; divoká zvířata; Bird Diseases; klíšťata; Mite Infestations; zvířata; Ticks; nemoci ptáků; Animals, Wild; Czech Republic; Tick Infestations; infestace klíšťaty